Legal pluralism in Mexico: current indigenous languages, extinct languages, and legal transcendence - Cristóbal Roldán, Dulce Getsemani (2023)
The juridical transcendence has great relevance for juridical pluralism in Mexico due to the historical background that constitutes the analysis of the juridical systems of the indigenous communities, the same that determine the qualification of pluricultural to this country and that count with the protection of article 2 of the Political Constitution of the United Mexican States. Likewise, the main tool for the recognition and preservation of the languages of these communities is the General Law of Linguistic Rights of Indigenous Peoples. However, despite this protection, there is evidence of a progressive loss of indigenous languages in terms of their use and customs. In this article, we will analyze this phenomenon from a statistical perspective to demonstrate that one of the factors influencing the loss of indigenous languages is the difficulty of access of their speakers to a good quality of life, since they are forced to leave their communities to acquire the resources they need, for which they must learn the dominant language, leaving their mother tongue in oblivion.